2005
DOI: 10.1002/jsfa.2368
|View full text |Cite
|
Sign up to set email alerts
|

Expression of basic genes involved in tea polyphenol synthesis in relation to accumulation of catechins and total tea polyphenols

Abstract: Catechins, a group of polyphenolic compounds in the green leaf of tea [Camellia sinensis (L.) O. Kuntze], are major components conferring quality attributes and health benefits on processed tea. Expression patterns of the basic genes related to accumulation of the catechins and total polyphenols at different stages of tea leaf development and their relationship with catechin concentration were investigated by reverse transcriptase polymerase chain reaction and high-performance liquid chromatographic methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 26 publications
(38 reference statements)
2
56
1
1
Order By: Relevance
“…The HPLC results from the experiment of Park et al [11] showed that the levels of EGC, EGCG, and ECG in South Korean young tea leaves were higher than in mature leaves. In contrast, from the study of Chinese tea cultivar Zhenong 139 by Mamati et al [5], the levels of EGC and ECG were higher in mature leaves than in young leaves, while the levels of C, EGCG, and GCG in the young and mature leaves did not show significant differences. These different results were possibly due to the differences in post-harvest treatments of the samples.…”
Section: Hplc Analysis Of Catechins In Tea Shoots and Mature Leavesmentioning
confidence: 53%
See 1 more Smart Citation
“…The HPLC results from the experiment of Park et al [11] showed that the levels of EGC, EGCG, and ECG in South Korean young tea leaves were higher than in mature leaves. In contrast, from the study of Chinese tea cultivar Zhenong 139 by Mamati et al [5], the levels of EGC and ECG were higher in mature leaves than in young leaves, while the levels of C, EGCG, and GCG in the young and mature leaves did not show significant differences. These different results were possibly due to the differences in post-harvest treatments of the samples.…”
Section: Hplc Analysis Of Catechins In Tea Shoots and Mature Leavesmentioning
confidence: 53%
“…In studies of tea catechins, it is necessary that the samples must be immediately treated with heat or liquid nitrogen in order to stop activities of an enzyme, polyphenol oxidase, otherwise, the results may not be accurate. In this study and the study of Park et al [11], the samples were treated with heat from microwave and liquid nitrogen, respectively, immediately after harvested, while in the study of Mamati et al [5], there was no post-harvest treatment mentioned. These might have led to the differences in the trends of the catechins accumulation.…”
Section: Hplc Analysis Of Catechins In Tea Shoots and Mature Leavesmentioning
confidence: 96%
“…Although, several independent studies have reported the expression profile of various genes of these pathways individually or in limited number in response to leaf age and different external cues in single varieties19202122232425. Also, these previous studies were limited either by gene studied, tissues, variety and/or season.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was extracted from leaf samples using the TRIzol reagent in accordance with the manufacturer's instructions (Invitrogen, USA), and the integrity and quality of the RNA were checked according to Mamati et al (2006). First-strand complementary DNA (cDNA) was synthesized using 1.0 µg total RNA with SuperScript Reverse Transcriptase (Invitrogen, USA).…”
Section: Cloning Of Csccoaomtmentioning
confidence: 99%